2003
DOI: 10.1002/cb.113
|View full text |Cite
|
Sign up to set email alerts
|

Are cultural differences overrated? Examining the influence of national culture on international buyer‐seller relationships

Abstract: The notion that differences in national culture influence international buyer-seller relationships (and, indeed, all aspects of international management) is not only held as true but also axiomatic. This study questions the degree to which cultural differences impact upon buyer-seller relations for seven key dimensions using Hofstede's indices of culture. Via two stages of data collection using two methodological approaches (seven interviews and 322 useable responses from a mail survey), the impact of culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…We will, therefore, draw upon different cross-cultural studies that have researched the cultural values, norms, routines, and customs in the two countries as proxies for national culture (Kluckhohn and Strodtbeck, 1960;Hall, 1976;Hofstede, 1980;Goodenough, 1981;D'Andrade, 1984;Hall and Hall, 1990;McCort and Malhotra, 1993;Trompenaars and Hampden-Turner, 1997;Hofstede, 2001). The applicability of Hofstede's framework to the context of buyer-seller relationships has been confirmed by a number of authors (Pressey and Selassie, 2003) and if used with caution and reasoning, cultural theory and anent studies can provide a useful basis for the explanation of distinctions found in different cultural contexts.…”
Section: Discussionmentioning
confidence: 87%
“…We will, therefore, draw upon different cross-cultural studies that have researched the cultural values, norms, routines, and customs in the two countries as proxies for national culture (Kluckhohn and Strodtbeck, 1960;Hall, 1976;Hofstede, 1980;Goodenough, 1981;D'Andrade, 1984;Hall and Hall, 1990;McCort and Malhotra, 1993;Trompenaars and Hampden-Turner, 1997;Hofstede, 2001). The applicability of Hofstede's framework to the context of buyer-seller relationships has been confirmed by a number of authors (Pressey and Selassie, 2003) and if used with caution and reasoning, cultural theory and anent studies can provide a useful basis for the explanation of distinctions found in different cultural contexts.…”
Section: Discussionmentioning
confidence: 87%
“…An uncertainty avoidance culture suggests that individuals express a preference for long-term predictability of rules, work arrangements, relationships, and avoidance of risk taking, and that they expend more effort on planning to reduce uncertainty (Hofstede, 1984;Pressey and Selassie, 2006). Newman and Nollen (1996) The ship is a closed society.…”
Section: H7: Confucian Dynamism Negatively Strengthens the Relationshmentioning
confidence: 99%
“…For example, Pressey and Selasie (2003) did not find a significant effect for national culture on international buyerseller relationships. They also cite a number of studies that report similar trends.…”
Section: A Single National Culturementioning
confidence: 78%